THE ENVIRONMENTAL STIMULI OF THE WEDDING DECORATION TOWARDS CUSTOMER SATISFACTION - Umbas, Prisciani Blesy (Jurnal Berkala Ilmiah Efisiensi, 2015)
ABSTRACT The rapid growth, economy crisis and the changing of consumer’s lifestyle emerge the challenge for the marketer in this era. Consumers have wide insight in order to satisfy their needs and wants. The study aims to analyze how the environmental stimuli of wedding decoration towards customer satisfaction. 100 people who experienced in the wedding decoration were surveyed as respondents. The result shows the wedding decoration, the environment is stimulating by visual and sound; touch; and taste and smell have influences toward customer satisfaction simultaneously and partially. And it shows that visual and sound have the most dominant influence toward customer satisfaction in wedding decoration partially compared to the other human senses, so the vendor has to think the creative ideas and concepts for making the surrounding can sensed by eye and ear, it is also about how to make a nice decoration with a blend of visual and sound. Keywords: Customer Satisfaction, Human Senses, Wedding Decoration, Wedding Service.